Black Watermelon Bug, Coridius viduatus (F.) (Heteroptera: Dinidoridae) in Hatay Region of Turkey - Şener Tarla; Halit Yetişir; Gülcan Tarla (Journal of Basic & Applied Sciences, 2013)
Black watermelon bug, Coridius viduatus (F.) (Heteroptera: Dinidoridae) is one of the most important pest of watermelon in many of African countries. This species is known to be present in Turkey. Although several studies on this species have been done in countries where it is present, it was not sufficiently studied in Turkey. This pest was observed first time on squirting cucumber [Ecballium elaterium (L.) A. Richard (Cucurbitaceae)] in Hatay province in 2004. This plant species is the natural host of several viruses creates significant problems in cucurbit plants in the Mediterranean basin. The studies were conducted in both laboratoryand natural conditions in 2007 and 2008. Biological stages of the pest was investigated and determined. Furthermore, damage of the pest on four different cucurbit species [watermelon (Citrullus lanatus Matsum. and Nakai), cucumber (Cucumis sativus L.), squirting cucumber (E. elaterium) and bottle gourd (Lagenaria siceraria (Molina) Stadl.)] was investigated. In these studies, it was observed that the pest was able to complete its life cycle when only squirting cucumber and watermelon were used as food sources.